Determination of Agrin and Related Proteins Levels as a Function of Age in Human Hearts - Skeffington, Katie L.; Jones, Ffion P.; Suleiman, M. Saadeh; Caputo, Massimo; Brancaccio, Andrea; Bigotti, Maria Giulia (Frontiers in Cardiovascular Medicine, 2022)
Background: Mature cardiomyocytes are unable to proliferate, preventing the injured adult heart from repairing itself. Studies in rodents have suggested that the extracellular matrix protein agrin promotes cardiomyocyte proliferation in the developing heart and that agrin expression is downregulated shortly after birth, resulting in the cessation of proliferation. Agrin based therapies have proven successful at inducing repair in animal models of cardiac injury, however whether similar pathways exist in the human heart is unknown. Methods Right ventricular (RV) biopsies were collected from 40 patients undergoing surgery for congenital heart disease and the expression of agrin and associated proteins was investigated. Results Agrin transcripts were found in all samples and their levels were significantly negatively correlated to age (p = 0.026), as were laminin transcripts (p = 0.023), whereas no such correlation was found for the other proteins analyzed. No significant correlations for any of the proteins were found when grouping patients by their gender or pathology. Immunohistochemistry and western blots to detect and localize agrin and the other proteins under analysis in RV tissue, confirmed their presence in patients of all ages. Conclusions We show that agrin is progressively downregulated with age in human RV tissue but not as dramatically as has been demonstrated in mice; highlighting both similarities and differences to findings in rodents. Our results lay the groundwork for future studies exploring the potential of agrin-based therapies in the repair of damaged human hearts.